Exploring student perceptions of offshoring. Issue 2 (July 2019) - Maloni, Michael J.; Swaim, James A.; Mutlu, Canan C.; Wermert, James
Abstract: The current escalating global tariff war reflects public concern with offshoring associated with perceived loss of jobs and reduced national competitiveness. Accordingly, offshoring represents a crucial yet complex topic in business education as existing literature emphasizes how managers struggle to make objective offshoring decisions. With limited available pedagogical research however, educators are not fully aware of how students perceive offshoring and process offshoring decisions. This study subsequently applies realistic conflict theory (RCT) to provide an empirical assessment of student offshoring perceptions via survey data at one U.S. university. The results do not support RCT as positive perceptions of offshoring benefits are insufficient to overcome the effects of career concerns. Rather, offshoring benefits directly conflict with career concerns to influence offshoring resentment, which in turn, impacts offshoring decisions. Such results suggest that students are unduly biased in their offshoring perceptions, thereby elevating the importance and difficulty of effective offshoring education. As such, we offer a pedagogical framework and associated exercises from extant literature to help students critically assess offshoring. Highlights: Limited research examines student offshoring perceptions. Student positive and negative offshoring perceptions affect offshoring resentment. Offshoring resentment subsequently biases offshoring decision making. A teaching framework is presented to enhance offshoring pedagogy.